2020
DOI: 10.21203/rs.3.rs-53417/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic vs. Extrinsic Motivation as Drivers for Early Engagement in Research by Medical Students

Abstract: BackgroundA student’s motivation is a key factor in their success in undertaking an education endeavour. However, how this relates to involvement in research by medical students is unclear.MethodsAn electronic questionnaire was sent to all medical students at our institution. To ascertain students’ motivation to undertake research, they were asked an open-ended question to describe the single major factor that would encourage them to get involved in research as a medical student. A framework of self-determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The URP is getting attention as an integral part of medical education. [1][2][3][4][5]13,14 This helps in critical analysis and leadership during the professional career. Early exposure to URP is a strong motivation to improve learning and for future specialization.…”
Section: Importance Of Research-oriented Physicians and Physician-sci...mentioning
confidence: 99%
See 2 more Smart Citations
“…The URP is getting attention as an integral part of medical education. [1][2][3][4][5]13,14 This helps in critical analysis and leadership during the professional career. Early exposure to URP is a strong motivation to improve learning and for future specialization.…”
Section: Importance Of Research-oriented Physicians and Physician-sci...mentioning
confidence: 99%
“…Study shows that influence of extrinsic motivation (e.g., improving biodata) may be of greater importance than intrinsic motivation (e.g., interest/passion) for medical students to get engaged in URP. 5 Medical students' participation in URP remains low despite the benefits, and thus there is a need to find out the obstacles identified by the students, and develop strategies to motivate them to increase their participation in research. 1,2,17,18…”
Section: Importance Of Research-oriented Physicians and Physician-sci...mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the recent article by Almari et al 1 regarding intrinsic motivation (IM) and extrinsic motivation (EM) in the context of medical student involvement in research. The study found that medical students who engaged in research were more likely to report EM.…”
Section: Dear Editormentioning
confidence: 99%
“…For us and many of our peers, the extra points are currently the main motivator to get involved in research, and we relate to the senior medical students in this study who were influenced by the looming deadline of intern applications. 1 …”
Section: Dear Editormentioning
confidence: 99%